Are Regulation and Innovation Priorities Serving Public Health Needs? - Milne, Christopher-Paul; Kaitin, Kenneth I. (Frontiers in Pharmacology, 2019)
A host of challenges confront healthcare authorities worldwide. Topping the list is the demand for innovative new medicines to treat a range of both infectious and non-communicable diseases, while containing spiraling healthcare costs. The challenge is particularly great in therapeutic areas where, despite significant medical need and economic impact, the technical challenges and commercial risk of development serve as disincentives to drug sponsors. These areas include cardiovascular diseases as well as diseases and disorders of the central nervous system. Currently, the development and approval of new active substances, with its disproportionate focus on oncology, is not in alignment with healthcare needs in most geographic regions. In this article, we discuss the origins of this misalignment and suggest various approaches to address healthcare needs going forward.